Lesbians and Space: An Interpretive Phenomenological Analysis - Prest, Dayna (Université d'Ottawa / University of Ottawa, 2016)
In a moment when visibility and representations of LGBTTQAI+ people are proliferating in North American society, it is important to think critically about how visibility and representations function and to interrogate their meanings and a/effects. This thesis uses data produced from five semi-structured interviews conducted with lesbian identified participants living in non-urban spaces in Ontario to demonstrate the importance of a continued lesbian specificity, to draw attention to heteronormativity and heterosexism in Ontarian society, to challenge femme invisibility and complicate the notion of femme privilege, and to move beyond the urban/rural binary as a way of making sense of sexuality. The methodological framework guiding this thesis draws on interpretive phenomenological analysis as well as feminist and queer methodologies, which facilitated a responsive and reflexive research process. This thesis is grounded in ongoing debates around identity politics and representation, drawing on literature from lesbian theories, lesbian-feminist histories, queer theories, heterosexism, heteronormativity and homonormativity, lesbian-feminist histories, white privilege studies, queer and feminist geography, and LGBTTQAI+ rural studies.
Keywords: lesbian studies; lesbian-feminism; heteronormativity; heterosexism; queer theories; white privilege studies; Ontario